2014
DOI: 10.1364/oe.22.023121
|View full text |Cite
|
Sign up to set email alerts
|

Field trial of a quantum secured 10 Gb/s DWDM transmission system over a single installed fiber

Abstract: We present results from the first field-trial of a quantum-secured DWDM transmission system, in which quantum key distribution (QKD) is combined with 4 × 10 Gb/s encrypted data and transmitted simultaneously over 26 km of field installed fiber. QKD is used to frequently refresh the key for AES-256 encryption of the 10 Gb/s data traffic. Scalability to over 40 DWDM channels is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…The leftmost point corresponds to a rate of 1.257 Mbit/s, a record in terms of key rate mediated by two-photon interference. The rightmost point corresponds to about 4 kbit/s over 21 dB attenuation, which is still sufficient to generate a 256-AES key more frequently than every 100 ms [26].Following the analysis in Ref.[27], we consider how the statistical fluctuations of a finite data sample can affect the secure key rate. With the empty square point in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The leftmost point corresponds to a rate of 1.257 Mbit/s, a record in terms of key rate mediated by two-photon interference. The rightmost point corresponds to about 4 kbit/s over 21 dB attenuation, which is still sufficient to generate a 256-AES key more frequently than every 100 ms [26].Following the analysis in Ref.[27], we consider how the statistical fluctuations of a finite data sample can affect the secure key rate. With the empty square point in Fig.…”
mentioning
confidence: 99%
“…The leftmost point corresponds to a rate of 1.257 Mbit/s, a record in terms of key rate mediated by two-photon interference. The rightmost point corresponds to about 4 kbit/s over 21 dB attenuation, which is still sufficient to generate a 256-AES key more frequently than every 100 ms [26].…”
mentioning
confidence: 99%
“…An increasing number of QKD quantum networks and field trials from all over the world have been reported recently [20][4] [5] showing the feasibility of QKD architectures that are far more complex than the original point-to-point dark fiber connection. The QKD ISG aims to assist the integration process by defining relevant standards for such efforts.…”
Section: The Main Advantage Of Qkd Is That It Is Informationmentioning
confidence: 99%
“…Underpinned by many new developments, including the establishment of a quantified security level [2], QKD technology has matured considerably in the last decade. Furthermore the technology is making the transition from the laboratory to successful field trials [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, operation of QKD systems usually required dedicated SSMFs, which are not only expensive but might even be unavailable. Multiplexing QKD into data-populated SSMF has been explored, but it constrains either the communication distance or the launched data laser power and maximum bandwidth [8,[18][19][20][21][22][23][24][25]. These constraints are a consequence of signal contamination to the quantum channel by the Raman photons generated by the strong data signals in the same fiber.…”
Section: Introductionmentioning
confidence: 99%